Meparishvili K.H. Modern institutional management system of water resources in Ukraine - Gryshyna, Nataliia (Pressing Problems of Public Administration, 2019)
The article outlines the modern system features in institutional management of water resources and hydrotechnical land reclamation, management, use and reproduction of surface water resources through the structural and functional management organization. There is the institutional model of the water resources management system in Ukraine in the article.